PEPPER FRUIT YIELD UNDER DIFFERENT FERTILIZER RATES IN REGIONS OF THE AMAZON - Fidelis, Iraci; Ramos, Isaellen Padrinho (Anais Eventos, 2026)
The municipality of Amajari is located in the northern region of Roraima, 156 km from the capital Boa Vista, and has 13,927 inhabitants. Rural producers use rudimentary techniques, do not receive training or incentives, and are not part of projects from public agencies. Thus, the adoption of public policies and technical support is essential to provide assistance to small-scale rural producers (MEGIDO, 2020). The objective was to evaluate pepper fruit yield under different fertilizer rates in regions of the Amazon. Under the studied conditions, it was observed that treatment A (300 kg/ha P₂O₅ and 240 kg/ha K₂O) provided the greatest increase in fresh and dry mass of pepper fruits, measured in grams.